Overlapping vitamin A interventions in the United States, Guatemala, Zambia, and South Africa: Case studies - Tanumihardjo, Sherry A.; Kaliwile, Chisela; Boy, Erick; Dhansay, Muhammad A.; van Stuijvenberg, Martha E. (John Wiley & Sons, 2019)
Vitamin A (VA) deficiency is a serious public health problem, especially in preschool children who are at risk of increased mortality. In order to address this problem, the World Health Organization recommends periodic high‐dose supplementation to children 6–59 months of age in areas of highest risk. Originally, supplementation was meant as a short‐term solution until more sustainable interventions could be adopted. Currently, many countries are fortifying commercialized common staple and snack foods with retinyl palmitate. However, in some countries, overlapping programs may lead to excessive intakes. Our review uses case studies in the United States, Guatemala, Zambia, and South Africa to illustrate the potential for excessive intakes in some groups. For example, direct liver analysis from 27 U.S. adult cadavers revealed 33% prevalence of hypervitaminosis A (defined as ≥1 μmol/g liver). In 133 Zambian children, 59% were diagnosed with hypervitaminosis A using a retinol isotope dilution, and 16% had ≥5% total serum VA as retinyl esters, a measure of intoxication. In 40 South African children who frequently consumed liver, 72.5% had ≥5% total serum VA as retinyl esters. All four countries have mandatory fortified foods and a high percentage of supplement users or targeted supplementation to preschool children.